2015
DOI: 10.1016/j.bandl.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a rhythm perception deficit in children who stutter

Abstract: Stuttering is a neurodevelopmental disorder that affects the timing and rhythmic flow of speech production. When speech is synchronized with an external rhythmic pacing signal (e.g., a metronome), even severe stuttering can be markedly alleviated, suggesting that people who stutter may have difficulty generating an internal rhythm to pace their speech. To investigate this possibility, children who stutter and typically-developing children (n = 17 per group, aged 6–11 years) were compared in terms of their audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 79 publications
5
61
0
2
Order By: Relevance
“…Finally, we observed a trend for AS to have lower scores on the music perception task, which is further evidence of perceptual differences between individuals who stutter and their fluent peers . This was true despite the fact that both groups had similar amounts of music training, and that scores on this task were relatively high.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Finally, we observed a trend for AS to have lower scores on the music perception task, which is further evidence of perceptual differences between individuals who stutter and their fluent peers . This was true despite the fact that both groups had similar amounts of music training, and that scores on this task were relatively high.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, it has been suggested that stuttering behavior may be related to a timing deficit that is sensorimotor in nature . Coupled with this are studies showing deficits in rhythm perception and motor sequence learning, leading to the idea that this sensorimotor timing deficit may extend to nonspeech . A number of studies over the years have attempted to demonstrate this by examining nonspeech timing with metronome synchronization in people who stutter.…”
Section: Introductionmentioning
confidence: 99%
“…Jungblut et al (2014), studying apraxia of speech in aphasic patients, have put forward the idea that singing may enhance and reeducate speech motor capacities, in particular temporal planning, programming and sequencing of speech movements via its rhythmic structure. Following this idea, the present study investigates temporal aspects of articulation in singing and perceptually fluent speech in stuttering, a speech fluency disorder that is characterized by deficits in speech motor control (e.g., Civier, Tasko,[ 6 4 _ T D $ D I F F ] & Guenther, 2010; Ludlow & Loucks, 2003;Namasivayam & van Lieshout, 2011;Zimmermann, 1980), but also potential deficits in temporal processing (Alm, 2004;Etchell, Johnson, & Sowman, 2014;Etchell, Ryan, Martin, Johnson, & Sowman, 2016;Falk, Müller, & Dalla Bella, 2015;Van Riper, 1982;Wieland, McAuley, Dilley, & Chang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As impairments in both rhythm perception and the precision of beat synchronization are found in a range of developmental disorders of language, including stuttering (Falk et al, 2015; Wieland et al, 2015) and speech and language impairment (Corriveau and Goswami, 2009; Cumming et al, 2015) as well as developmental dyslexia, it is of theoretical interest to ascertain the sensory and/or motor sources of impaired sensorimotor synchronization in children with different disorders. The identification of underlying neural mechanisms would help to optimize remediation.…”
Section: Introductionmentioning
confidence: 99%